PENGEMBANGAN MEDIA PEMBELAJARAN RUBERGI (RUMAH SUMBER ENERGI) BERBASIS MEDIA 3 DIMENSI - Alifia Munaamah; Encep Andriana; Ahmad Syachruroji (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to determine how to develop Rubergi (Rumah Sumber Energi) Learning Media based on 3-D media at grade IV, to determine the feasibility of Rubergi learning media, and to determine students’ responses to rubergi learning media. This research was conducted at SDN Toyomerto 2, which involved 33 grade IV students. 13 students were on a limited trial. This type of research utilized the Trianto development model. This development consisted of the Definition Stage (Define), the Design Stage (Design), and the Development Stage (Develop). However, the research was limited to the development stage (Develop), which was only up to the final product stage. The instruments used were in the form of a questionnaire sheet for media validation by the lecturer and a students’ response questionnaire sheet. Based on the data analysis, it was concluded that the feasibility of Rubergi learning media was in very feasible category with a percentage of 87.14% from two media experts, in very feasible category with a percentage of 81.73% from two material experts, and in very feasible category with a percentage of 84.5% from two education experts. The students’ responses to Rubergi learning media in a trial with 13 respondents were 85.72% in the very good category. Based on these results, the final product, Rubergi learning media, was feasible to be used in the learning activities for grade four elementary school students.